2011
DOI: 10.1128/jcm.00210-11
|View full text |Cite
|
Sign up to set email alerts
|

Culture Phenotypes of Genomically and Geographically Diverse Mycobacterium avium subsp. paratuberculosis Isolates from Different Hosts

Abstract: Mycobacterium avium subsp. paratuberculosis causes paratuberculosis (Johne's disease) in ruminants in most countries. Historical data suggest substantial differences in culturability of M. avium subsp. paratuberculosis isolates from small ruminants and cattle; however, a systematic comparison of culture media and isolates from different countries and hosts has not been undertaken. Here, 35 field isolates from the United States, Spain, Northern Ireland, and Australia were propagated in Bactec 12B medium and Mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 45 publications
3
45
0
2
Order By: Relevance
“…According to Withlock et al (2000), the disadvantages of some detection test are due mainly because of the intermittent shedding of microorganisms. This means that the sensitivity of direct tests to detect symptomatic animals is high, but low for detection of infected/subclinical animals (Nielsen and Toft, 2008;Schönenbrücher et al, 2008;Whittington et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Withlock et al (2000), the disadvantages of some detection test are due mainly because of the intermittent shedding of microorganisms. This means that the sensitivity of direct tests to detect symptomatic animals is high, but low for detection of infected/subclinical animals (Nielsen and Toft, 2008;Schönenbrücher et al, 2008;Whittington et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the specificity of fecal culture is considered to be almost 100% if the isolates obtained are confirmed to be MAP by molecular methods such as polymerase chain reaction (PCR; Nielsen and Toft, 2008;Schönenbrücher et al, 2008;Whittington et al, 2011). Fecal culture has been used as an acceptable standard technique for detecting the infection status of animals -related to elimination rate-, for estimating the sensitivity of other diagnostic tests (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…One of the important drawbacks of culture is its sluggishness associated with requirement of mycobactin J and high costs. The addition of mycobactin J in the medium is the primary requirement for in vitro culture of MAP enabling iron acquisition and its dependence can be used as discriminatory tests for confirmation of MAP in culture (Whittington et al 2011). Use of automated systems such as BACTEC MGIT 960 shortens the time of detection (4À7 weeks) and can detect as low as 10 CFU/ml .…”
Section: Fluorescent Microscopymentioning
confidence: 99%
“…Thus, environmental and host factors may potentially influence the phenotype of MAP prior to and during infection. Early studies on this phenomenon have identified a variety of phenotypes between geographically distinct MAP isolates (Whittington et al, 2011), and have illustrated proteomic differences between laboratory culture and mucosal derived isolates (Weigoldt et al, 2011). MAP also develops a more invasive phenotype in response to both the hyperosmolar environment of raw milk and growth within the mammary epithelium (Patel et al, 2006).…”
Section: Introductionmentioning
confidence: 99%